The Impact of Literacy, Religiosity, and Technology on Students' Interest in Cash Waqf - Tazkia, Nur Hitmi; Tanjung, Hendri; Arif, Suyud (International Journal of Waqf, 2024)
The results of the 2020 Waqf Literacy Index (ILW) survey by the Indonesian Waqf Agency, the Center for Strategic Studies BAZNAS & the Directorate of Empowerment of Zakat and Waqf Ministry of Religion of the Republic of Indonesia show that the ILW score nationally scores 50.48 which is in the low category. This study aims to determine the effect of literacy, religiosity and technology on interest in cash waqf of students of Islamic Economics, University of Ibn Khaldun, Bogor. The data and information in this study used primary data obtained from filling out the questionnaire. The population in this study amounted to 109 students, using Proportionate Stratified Random Sampling and the slovin formula, the sample of this study consisted of 86 respondents. The type of data used is quantitative and uses multiple linear regression analysis methods. The results of this study simultaneously literacy, religiosity and technology have a significant effect on interest in cash waqf. Partially, literacy and religiosity have a significant effect on interest in cash waqf, while technology does not have a significant effect on interest in cash waqf.